RELATIONAL CAPABILITY AND MARKET ACCESS IN MSMEs: LINKING SOCIAL CAPITAL, COLLABORATION, AND COMPETITIVE ADAPTATION - Anggun Yolistina; Nazhira Nindya Padma Hanuun (Journal of Jabar Economic Society Networking Forum, 2025)
This conceptual paper develops an integrative framework for relational capability and market access in MSMEs in micro, small, and medium enterprises (MSMEs). It synthesizes established literature on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial ecosystems. The analysis explains how relational trust, bridging networks, market information, collaboration discipline, and opportunity access can be organized into proportionate managerial routines. No primary survey, interview, experimental, or statistical data are claimed. The framework proposes diagnosis, capability mapping, bounded experimentation, evidence review, governance, resource reconfiguration, and learning retention as a cumulative cycle. Implications are developed for owner-managers, support institutions, and future empirical research.